The Need for Enhancement of Information Technology Education at Universities Training Business Students - Denis VASILIEV (Communications of International Proceedings, 2021)
Digital transformation currently is one of the most important trends in business. Applications of digital tools in business are diverse, including e-commerce, marketing, customer relationship management, human resource management, business process automation, logistics management, entrepreneurial resource planning, business analytics, international trade etc. A range of digital tools is ample and choice of the right tools as well as the ability to use them is fundamental to achievement of sustainable competitive advantage and long-term prosperity of the modern enterprise. Recent advances in the area of machine learning and artificial intelligence if applied correctly can fundamentally improve quality of business operations and deliver unprecedented levels of value to customers. Choice of technology often determines business scalability and ability of the company to compete with other organizations. Furthermore, technological decisions usually require understanding of cost-benefit ratio of different information technology solutions. The risk of making wrong decisions may be particularly high at small companies and startups that do not possess substantial financial resources. Yet it is not clear to what extent are future business leaders capable to make informed information technology choices. Essential knowledge among the future business leaders and manager may be obtained if it is taught at universities training business students. In order, to understand whether the level of information technology training is sufficient at universities teaching business students a survey of 100 international students from a range of universities was conducted. Results suggest that the level of awareness of modern information technologies applicable in business is low, which clearly indicates the need to enhance education in this area.
Keywords: Digital Tools; E-Commerce; Programming; Big Data; Artificial Intelligence; Business Education.